1992
DOI: 10.1002/jcp.1041530319
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a chinese hamster ovary cell line that expresses grp78 antisense transcripts and suppresses A23187 induction of both GRP78 and GRP94

Abstract: GRP78, a 78,000 dalton protein residing in the endoplasmic reticulum, is postulated to play important roles in protein folding and cell survival during calcium and other physiological stress. Here we describe the construction of an eukaryotic expression vector for the constitutive expression of grp78 antisense RNA and the creation of a CHO cell line, 78WO, which expresses high levels of the grp78 antisense RNA through amplification of the stably transfected antisense vector. We observed that whereas 78WO maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 33 publications
(31 reference statements)
3
66
0
1
Order By: Relevance
“…Conversely, inhibition of GRP induction increases sensitivity to death in response to calcium release from the ER (Li et al 1991(Li et al , 1992, oxidative stress (Gomer et al 1991), hypoxia (Koong et al 1994b), and T cell mediated cytotoxicity (Sugawara et al 1993). Therefore, elucidating the signaling mechanism(s) by which cells respond to ER stress may have important therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of GRP induction increases sensitivity to death in response to calcium release from the ER (Li et al 1991(Li et al , 1992, oxidative stress (Gomer et al 1991), hypoxia (Koong et al 1994b), and T cell mediated cytotoxicity (Sugawara et al 1993). Therefore, elucidating the signaling mechanism(s) by which cells respond to ER stress may have important therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing the induction of GRPs through transfection of BiP antisense RNA expression constructs, transfection of anti-BiP ribozymes, or transfection with multiple copies of the BiP promoter element to titrate out positively acting transcription factors increased sensitivity to ionophore, oxidative stress, hypoxia, and cell-mediated toxicity (Gomer et al 1991;Li and Lee 1991;Li et al 1992;Sugawara et al 1993;Koong et al 1994). In contrast, overexpression of BiP itself prevented transcriptional induction in response to ER stress and protected cells from death in response to calcium depletion from the ER (Dorner et al 1992;Morris et al 1997).…”
Section: Regulation Of Grp Inductionmentioning
confidence: 99%
“…Recently, it has been shown that a variety of toxic insults, including calcium ionophores, inhibitors of glycosylation, chemical toxicants, and oxidative stress, can cause ER stress and ultimately lead to cell death. [31][32][33][34][35][36][37][38][39] We found that significant ER stress and resultant apoptosis occurred in cells expressing mutated COMP compared with wild-type COMP and discuss the significance of this in PSACH.…”
mentioning
confidence: 99%